2009
DOI: 10.1517/17425240903338055
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-based vaginal drug delivery systems for HIV prevention

Abstract: To date, few studies have been published that exploit nanoparticle-based microbicidal delivery to the vagina. The use of nanoparticles for vaginal drug delivery provides an approach to overcome the existing barriers to success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 90 publications
1
68
0
1
Order By: Relevance
“…29,30 However, the drug release kinetics as well as drug loading could be improved by increasing the size of the nanoparticles. 31 It was found in our preliminary study that spray-dried NCs exhibited an average size ranging between 100 and 500 nm; therefore, our optimization goal was set to maximize EE% while minimize size within this range as further specified in the Results and Discussion section.…”
Section: Box-behnken Experimental Designmentioning
confidence: 99%
“…29,30 However, the drug release kinetics as well as drug loading could be improved by increasing the size of the nanoparticles. 31 It was found in our preliminary study that spray-dried NCs exhibited an average size ranging between 100 and 500 nm; therefore, our optimization goal was set to maximize EE% while minimize size within this range as further specified in the Results and Discussion section.…”
Section: Box-behnken Experimental Designmentioning
confidence: 99%
“…In recent years, studies have reported that the small size of nanocapsules enables them to penetrate cells and deliver drugs intracellularly without suffering extracellular degradation. 43,44 Moreover, controlled release systems can prolong the release and increase the contact time between the drug and the skin. 21 In addition, LNC-Hst increased the retention of the drug in the stratum corneum, possibly due to its rigid structure, 45 which maintains controlled release of the drug in the skin.…”
mentioning
confidence: 99%
“…39 Previous studies have established effective and safe intracellular delivery of antiretroviral drugs into human peripheral blood mononuclear cells or human monocyte/macrophage by NPs. 40,41 Further studies have also demonstrated favorable antiretroviral efficacy against HIV-1 when the drug is delivered into human monocyte-derived macrophages.…”
Section: Discussionmentioning
confidence: 99%